Evaluation of strobilurin fungicides Ergon 44.3% (w/w) [Kresoxim methyl 500 g L-1 SC] and RIL-070/FI (72WP) against Phytophthora capsici infection in black pepper - C R Anjali, R S Bhai, (Journal of Spices and Aromatic Crops, 2015)
Two new strobilurin fungicides viz., Ergon 44.3% (w/w) [Kresoxim methyl 500 g L-1 SC] and RIL-070/FI (72WP) were evaluated in vitro and in planta against Phytophthora capsici causing foot rot disease of black pepper and ED50 and ED90 values were calculated based on the in vitro efficacy. The chemicals were tested in planta using the maximum concentration found effective in vitro. Ergon when tested from 10-6000 ppm of the product in vitro, showed complete inhibition of mycelial growth and sporulation at 6000 ppm. But the zoospore germination was completely inhibited at 2000 ppm. The average ED50 and ED90 values of Ergon were 845.51 and 1740.71, respectively. Foliar spray of the chemical followed by challenge inoculation showed an overall reduction of lesion development by 44.83% over control and maximum inhibition (57.12%) was observed at five days after spraying at a concentration of 7000 ppm. Soil application of Ergon at different concentrations from 6000-8000 ppm showed no infection or mortality at 7000 ppm. RIL-070/FI at different concentrations from 10-500 ppm of the product when tested in vitro against P. capsici showed 100% mycelial inhibition at 50 ppm with ED50 and ED90 values of 22.85 and 45.71, respectively. For inhibition of sporulation, the maximum concentration required was 100 ppm. However, zoospore germination showed 100% reduction at 200 ppm. Foliar spraying of the RIL at concentrations from 100-600 ppm showed lesion development from 0.71 to 100%. When P. capsici was challenged five days after spraying of the chemical, 600 ppm showed 100% inhibition of lesion development.